The number of trichoma leaves, preference of Bemisia tabaci, and resistance soybean genotype against cowpea mild motle virus after treatment variation doses of Nitrogen - Endrik Nurrohman; Siti Zubaidah; Heru Kuswantoro (UNIVERSITAS NEGERI PADANG, 2022)
Bemisia tabaci is a dangerous insect for soybeans because it attacks the leaves and is a major obstacle in soybean cultivation and is considered a vector of Cowpea Mildmotle Virus (CpMMV). The part of the plant that defends itself from invading organisms is the trichome. Nitrogen nutrients can increase the number of trichomes in plant. This type of research is experimental research. The study design is a factorial design which is maintained in a complete group of randomized groups (RAKL). The first factor was a nitrogen dose consisting of four levels, such as N1 (0g), N2 (0.180g), N3 (0.36g), and N4 (0.543g), while the second factor was a genotype consisting of seven soybean genotypes UM.4-1, UM.7-2, UM.2-4, UM.7-6, UM.6-2, Wilis and Gumitir varieties. The results showed that there was a significant relationship between the number of upper trichomes and lower trichomes with the number of Bemisia tabaci. The interaction treatment had significant effect on the amount of upper surface of leaf tricoma and lower surface of leaf. Treatment of 0,543/ polybag nitrogen dose gave the most significant influence to the number of upper trichomes and lower trichomes. The results of correlation-regression analysis show that the number of lower trichomes contributes 65.7% in describing the number of Bemisia tabaci. The number of upper trichomes contributed 89.4% in describing the number of B. tabaci. Plants with a large number of trichomes and dense have low Bemisia tabaci preference and resistance to Cowpea Mild Motle Virus attacks in high level.Bemisia tabaci merupakan serangga berbahaya bagi kedelai karena menyerang daun dan menjadi kendala utama dalam budidaya kedelai dan dianggap sebagai vektor Cowpea Mildmotle Virus (CpMMV). Bagian tumbuhan yang mempertahankan diri dari serangan organisme pengganggu adalah trikoma. Unsur hara nitrogen dapat meningkatkan jumlah trikoma pada tanaman. Jenis penelitian ini adalah penelitian eksperimen. Desain penelitian adalah desain faktorial yang dipertahankan dalam kelompok lengkap kelompok acak (RAKL). Faktor pertama adalah dosis nitrogen yang terdiri dari empat taraf yaitu N1 (0g), N2 (0,180g), N3 (0,36g), dan N4 (0,543g), sedangkan faktor kedua adalah genotipe yang terdiri dari tujuh genotipe kedelai. Varietas UM.4-1, UM.7-2, UM.2-4, UM.7-6, UM.6-2, Wilis dan Gumitir. Hasil penelitian menunjukkan bahwa terdapat hubungan yang signifikan antara jumlah trikoma atas dan trikoma bawah dengan jumlah Bemisia tabaci. Perlakuan interaksi berpengaruh nyata terhadap jumlah permukaan atas daun trikoma dan permukaan bawah daun. Perlakuan dosis nitrogen 0,543/polybag memberikan pengaruh paling nyata terhadap jumlah trikoma atas dan trikoma bawah. Hasil analisis korelasi-regresi menunjukkan bahwa jumlah trikoma bawah berkontribusi 65,7% dalam menggambarkan jumlah Bemisia tabaci. Jumlah trikoma atas memberikan kontribusi 89,4% dalam menggambarkan jumlah B. tabaci. Tanaman dengan jumlah trikoma yang banyak dan lebat memiliki preferensi Bemisia tabaci yang rendah dan ketahanan terhadap serangan Cowpea Mild Motle Virus pada tingkat yang tinggi.